A study of the proficiency levels of the seniors of seven high schools of Laoag City in mathematics during the school year 1971-1972 - Blanco, Nenita (Pati) 1948- (s.n.], 1973)
This study sought to determine the proficiency levels in mathematics of senior students in seven high schools of Laoag City. A test was constructed to measure the proficiency levels and it included three subject areas: understanding mathematical concepts; proficiency in the fundamental operations; and proficiency in problem solving.